A study of the effect of PEG-40 surfactant concentration on the stability of microbubbles post-injection through various needle sizes and its ultrasound imaging performance - Das, Dhiman (2020)
Microbubbles stabilized by surfactant shells have been established as ultrasound contrast agents for the past several decades. The microbubbles often get destroyed as these are delivered to the region of interest using catheters with different needle sizes. Optimizing the concentration of the surfactants on its shell is crucial for minimizing microbubble destruction. In terms of shell material for this work; polyoxyethylene glycol 40 (PEG-40) stearate which is a non-ionic surfactant, polypropylene glycol and glycerol were used to stabilize the microbubbles with a nitrogen gas core. Presence of surfactants greatly influence the size and stability of the microbubbles and thus four different surfactant concentrations (2, 5, 10 and 15%) of PEG-40 and two different polypropylene glycol + glycerol (GPW) mixtures (10% and 15%) were examined. Nitrogen microbubbles were synthesized through high-shear rotor homogenizer and pushed through three different needle sizes (23, 27 and 30 gauge) using a syringe pump to examine their sensitivity to needle injection. A sample volume of 100 μl containing microbubbles were collected at a constant flow rate of 43.63 ul/min which is the maximum flow rate of the syringe pump used in our experiments. The microbubbles collected at the outlet of the needles were sandwiched between two glass slides for their stability characterization using optical microscopy. The results demonstrated that solution containing 10% PEG-40, 10% polypropylene glycol and 10% glycerol had the highest concentration of microbubbles post injection for all three needle sizes. Finally, phantom experiments were conducted to calculate the signal-to-noise (SNR) ratios of the microbubbles with the different surfactant concentrations using a clinical ultrasound system.